The Use of Information Technology in Managing The Supply Chain of Malaysian Palm Oil Industry: The Case of FELDA - Kamarulzaman, Nitty Hirawaty (2002)
This study was carried out to investigate the use of information technology (IT) and information systems (IS) by Malaysian palm oil industry in managing their supply chain. This study focused on Felda's palm oil supply chain which comprised of its subsidiary companies namely Felda Plantations Sdn. Bhd., Felda Palm Industries Sdn. Bhd., Felda Vegetable Oil Products Sdn. Bhd., Felda Transport Services Sdn. Bhd. and Felda Marketing Services Sdn. Bhd.. Investigation was also made to examine the extent of these palm oil companies in managing their primary and support activities and how IT and IS support those activities to improve the company's supply chain. In addition, the study was also done to investigate the utilization of IT and IS in all levels and activities of the company's supply chain. Data for the study were obtained through close-ended questionnaires that were mailed to the respondents comprised of managers from Felda's companies that were involved along supply chain. Data collected from the survey were analyzed using descriptive analysis, regression analysis, correlation analysis and reliability analysis.Result showed that Felda has effectively managed its primary activities particularly in estates, palm oil mills and refineries. Felda also has managed its inbound and outbound logistics as well as its marketing activities effectively. However, the results revealed that IT has not been fully used to effectively support certain primary and support activities, particularly in estates operations. However, while IT has made a lot of contribution to support palm oil mills support activities, it has made less contribution to support their primary activities. Further, IT has contributed significantly to support refineries' primary and support activities. At the same time, the results revealed that IT has effectively support distribution and marketing activities. From the findings, several recommendations are given to assist Felda and other palm oil based companies to enhance the management of their activities along their supply chain and help them to be more competitive in the industry.